Crecimiento, dimorfismo sexual y desnutrición: una reseña desde la antropología biológica experimental y comparativa - Oyhenart, Evelia Edith (2017)
Growth and sexual dimorphism reflect the interaction between genetic composition and the capacity of human beings to respond to different environments. The underlying environmental factors cannot be easily detected with comparative methods, even though evidence in the literature suggests that nutritional factors may cause variations in growth and sexual differentiation patterns. In this regard, the results published by Pucciarelli in his doctoral thesis in 1971 showed that comparative studies in Biological Anthropology were not absolutely concluding. In cases of two or more contradictory explanations for the same factor supported by comparative evidence, the procedure applied had methodological limitations. Thus, Pucciarelli distinguished a clear function of the experimental method in Biological Anthropology, settling a question difficult to solve by comparative methodology. Here we present a review of the work by Héctor Pucciarelli and associate researchers addressing growth and sexual dimorphism through experimental models, employing rodents and primates, and later in human populations.